The Effect of Small-Sided Games Training on Improving Futsal Player Agility - Faisal, Muhammad Ivan; Saputra, Mochamad Yamin; Nurcahya, Yudi (Ilmu Olahraga, 2025)
Agility is one of the physical demands needed in futsal. One effort to improve agility is through small-sided games training. Agility has a vital function, especially in coordinating multiple or simultaneous movements, facilitating mastery of techniques, and allowing players to accelerate when tricking opponents, and effectively utilizing relatively narrow spaces both when attacking and defending. This study aims to determine the effect of small-sided games training on improving the agility of futsal players. This research method uses an experiment with a pretest-posttest control group design involving 24 futsal players. Sample selection uses the Total Sampling Technique, with 12 treatments. This research instrument uses the Illinois Agility Test to measure the player's abilities before and after being given treatment. After the data is obtained, it is analyzed using SPSS Version 26 using the t-test. the calculated t value is 6.051 with a Sig. value. (2-tailed) of 0.000 and for conventional training results the calculated t is 3.997 with a Sig. value. (2-tailed) of 0.002. Based on the test results, the Sig. (2-tailed) value of both treatments Sig. <0.05 so that H0 is rejected. For the results of the Independent sample t-test which aims to determine the difference in the influence of different treatments, the Sig. (2-tailed) value is 0.011 <0.05. So it can be stated that there is a significant difference in the influence of small-sided games training with conventional training on the agility of futsal players. The conclusion of this study is that the small-sided games training method has a more significant effect than conventional training on the agility of futsal players. The recommendation from this study, to improve the agility of futsal players, it is better to apply small-sided games training than conventional training